Kualitas Pembelajaran Mahasiswa Selama Kuliah Online - Widayat, Prama (Jurnal Penjaminan Mutu, 2021)
Between the world of education and technology cannot be separated because these two sides are interrelated, student learning can be done online and offline by looking at the situation and conditions. The abilities and limitations they have are also different, so there is a need for a policy by dividing the zones in implementing online lectures based on the quality of the internet network owned by each region where the student comes from. The quality of the learning process can be seen from the quality of the lecturers who teach and the learning media used, especially in online learning everything has to adjust. The problem of an unstable internet network and lecturers who are not fully ready to teach online are the main problems in online learning. So that is the importance of dividing 3 zones for the application of online lectures, zone 1 network is strong and stable can study online, zone 2 network is less strong and stable, online and offline lectures and zone 3 networks are not yet available so offline lectures are conducted